STEM-BASED PHYSICS MODULES: A PRACTICAL APPROACH TO DEVELOPING CONCEPTUAL UNDERSTANDING IN TEACHER EDUCATION - Bahtiar, Bahtiar; Maimun, Maimun; Ibrahim, Ibrahim (MO.RI Publishing, 2024)
STEM (Science, Technology, Engineering, and Mathematics) based learning approaches are increasingly recognized as an effective method in increasing understanding of physics concepts for prospective teachers. This research aims to evaluate the implementation of learning, lecturer responses, and student responses to STEM-based teaching modules in Basic Physics courses for prospective physics teachers at UIN Mataram. This research uses a quantitative research method with a descriptive design, which involves collecting data through learning accessibility observation sheets and questionnaires to measure lecturer and student responses to the implementation of the module. The research results show that the STEM-based teaching module in the Basic Physics course has proven to be practical in implementing basic physics learning, and has received positive responses from lecturers and students. Based on these findings, it is recommended that STEM-based teaching modules be further improved in the aspects of material visualization and time management to better support more effective learning.